Investigation of E-Core Modular Permanent Magnet Wind Turbine - Aimeng Wang; Shanshan Li (Energies, 2020)
Under the adverse trend of fossil energy attenuation and air pollution, wind power effectively alleviates the global energy crisis and environmental pollution. For wind turbines, especially large offshore wind turbines, their transportation, installation, and maintenance are very inconvenient. In order to solve this problem, this paper presents an E-core stator modular machine which inserts stator gap into the unwounded teeth of the fractional-slot concentrated winding (FSCW) permanent magnet (PM) machine. The winding factor of the new stator structure machine was derived. The electromagnetic models of 12-slot/10-pole and 12-slot/14-pole modular FSCW PM machines and traditional FSCW PM machines were established using the finite element analysis (FEA) software, and the open-circuit flux density, cogging torque, load torque, loss, and efficiency were simulated and analyzed. The results showed that the modular structure of E-core stator not only simplified the transportation, installation, and maintenance of wind turbines, but also optimized the electromagnetic performance of the 12-slot/14-pole machine, i.e., improved the output torque and operation efficiency.